Clinical and Economic Impact of Time From Admission for CSF Rhinorrhea to Surgical Repair. (7th September 2018) - Villwock, Jennifer A.; Villwock, Mark R.; Deshaies, Eric M.; Goyal, Parul
Abstract : Background: If conservative management of CSF leak is unsuccessful, surgical repair is indicated for the prevention of severe complications such as meningitis. This study investigated the influence of surgical timing on clinical and economic outcomes. Methods: Retrospective review of the National Inpatient Sample (2012) and the Nationwide Inpatient Sample (2002–2011) for nonelective admissions with a principal diagnosis of CSF rhinorrhea treated with surgical repair of the meninges. Demographics and outcomes of patients undergoing meningeal repair for CSF rhinorrhea were analyzed. Cases were classified into four groups based on timing of surgical intervention: 1) performed on the day of admission (day 0), 2) performed between days 1 and 3, 3) performed between days 4 and 7, and 4) performed between days 8 and 14. Results: A total of 1, 088 emergent admissions were analyzed. On average, patients underwent surgical repair between the second and fourth day of admission. Lowest rates of meningitis were in patients treated on the day of admission (6.1%); those treated at 2 weeks had a 34.7% incidence. Multivariate analysis controlling for comorbidity burden, gender, and surgical timing found the highest odds of meningitis in patients treated with surgical repair during the second week of admission compared to repair on the day of admission (OR 8.2, P < .001). Length of stay (LOS) and hospital costs increased as time to repair increased. Conclusion: Multiple factors influence outcomes in patients with CSF rhinorrhea. Early surgical repair was significantly associated with decreased rates of meningitis, LOS, and hospital costs. Expedient treatment of patients admitted for CSF rhinorrhea may prove to be both a cost‐ and morbidity‐saving measure. Level of Evidence: 2C Laryngoscope, 129:539–543, 2019